KEPEMIMPINAN MORAL SPIRITUAL KEPALA PAUD DALAM MENINGKATKAN PEMBELAJARAN KARAKTER ANAK USIA DINI - BAHARUDDIN BAHARUDDIN; ELIHAMI ELIHAMI; IMRON ARIFIN; BAMBANG BUDI WIYONO (Universitas Muhammadiyah Prof Dr Hamka, 2017)
Early childhood education is a fundamental educational process. Children at an early age will be very easy to imitate or imitate whatever they see so that with the ability of the principal to show leadership that accentuated the moral aspect of spirituality will be able to help young children in shaping his character. This study aims to find out how the leadership of a moral-based spiritual principal able to improve character learning. The research method used descriptive qualitative approach. The results showed that through the approach of spiritual moral leadership three stages in the formation of the moral karingek knowing; moral feeling; and moral action more easily implemented through the learning process.